Pengembangan Aplikasi Pariwisata Kabupaten Jember berbasis Mobile - Andrew Adi Nugraha; Issa Arwani; Tibyani Tibyani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Tourism is a source of regional income that can be said to be endless or timeless, because generally tourism objects are natural tourism. Tourism will of course continue to be developed and promoted by each region in their own way. However, when this method is successfully implemented in a region, similar promotion methods will emerge in other regions with the same objectives. As happened at the Jember Fashion Carnival (JFC). Now, promotional strategies and efforts to attract tourists to come to other areas that have the same concept as JFC are starting to emerge. So, the Jember Regency government needs to find other ways to promote. However, apart from promotional measures, there are other things that should also be prioritized, namely information. So, an application, can provide a solution to handle both.This study aims to develop an application that can provide information about tourism objects in Jember Regency. The information referred to is the name, image, rate, description and route to the tourism object. The application is developed using the Java programming language and uses services from the Google Maps API to display maps and routes. The application is developed using the prototyping method, where a system requirement analysis will be formulated after the prototype is approved. For testing, the application will be tested using the black box approach for functional testing and usability testing and responsiveness for non-functional testing. The application that was successfully developed in this study is an application that can provide information on tourism objects, travel agencies and routes to tourism objects used by users, as well as web-based applications used by administrators to store, update and delete data. The test results for the application show valid results for functional testing and a fairly good results for non-functional testing.